2002
DOI: 10.1002/dvdy.10094
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and growth factor expression in abnormally enlarged placentas of mouse interspecific hybrids

Abstract: It has been shown previously that abnormal placental growth occurs in crosses and backcrosses between different mouse (Mus) species. In such crosses, late gestation placentas may weigh between 13 and 848 mg compared with a mean placental weight of approximately 100 mg in late gestation M. musculus intraspecific crosses. A locus on the X-chromosome was shown to segregate with placental dysplasia. Thus in the (M. musculus ؋ M. spretus)F1 ؋ M. musculus backcross, placental hyperplasia cosegregates with a M. spret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…A decreased expression of the X-chromosomal Esx1 gene was detected in abnormally enlarged placentas of mouse interspecif hybrids [13]. Moreover, further investigation of gene expression with interspecies hybridization, cloning by nuclear transfer, and mutation of the Esx1 gene revealed that genes whose expression is altered in abnormal placental growth are likely to be important in the occurrence of placentopathies [14].…”
Section: Discussionmentioning
confidence: 96%
“…A decreased expression of the X-chromosomal Esx1 gene was detected in abnormally enlarged placentas of mouse interspecif hybrids [13]. Moreover, further investigation of gene expression with interspecies hybridization, cloning by nuclear transfer, and mutation of the Esx1 gene revealed that genes whose expression is altered in abnormal placental growth are likely to be important in the occurrence of placentopathies [14].…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, dysmorphic development of spongiotrophoblast cells is also a characteristic of interspecies hybrid and cloned placentas (Rogers & Dawson 1970, Zechner et al 1996, Kurz et al 1999, Tanaka et al 2001. Abnormalities in genomic imprinting are implicated in these placental pathologies (Zechner et al 2002, Schutt et al 2003, Shi et al 2004, Singh et al 2004. There is some evidence for imprinting among members of the placental PRL family in Peromyscus (Vrana et al 2001); however, experimentation on imprinting within the rat PRL family locus has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…On the X chromosome, the genetic interval associated with hyperplastic placentas is large (between the centromere and 50 cM) (26). Esx1 (57 cM) may represent one of the genes associated with this phenotype since Esx1 mutants have a hyperplastic placenta and the expression of Esx1 is reduced in the placentas of interspecific hybrids (35,77). It would be interesting to examine the expression of Cited1 in the placentas of interspecific hybrids since the gene is located at 40.1 cM and there is an increase in spongiotrophoblasts in the Cited1 mutant placenta.…”
Section: Vol 24 2004mentioning
confidence: 99%